Oman : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Oman. (IMF Staff Country Reports; Country Report ;, 2021)
Sultan Haitham ascended to the throne in January 2020 and has committed to implementing strong fiscal and structural reforms to address longstanding vulnerabilities. In addition to persistent fiscal deficits arising from incomplete adjustment to lower oil prices since 2015, Oman faced twin shocks from the COVID-19 pandemic and a collapse in oil prices in 2020 that amplified fiscal and external vulnerabilities. The authorities moved rapidly to contain the spread of COVID-19 infections and provided broad-based policy measures to limit its impact on the economy. In addition, frontloaded fiscal consolidation has been implemented in the 2021 budget as part of the authorities' Medium-Term Fiscal Plan (MTFP) which aims to eliminate the fiscal deficit over the medium term. Banks have high capital buffers and liquidity, but credit risk is a concern going forward. Structural reforms have been accelerated under Oman Vision 2040 to boost non-oil private sector growth and facilitate job creation.